2018
DOI: 10.1177/0269215518819706
|View full text |Cite
|
Sign up to set email alerts
|

Providing exercise instructions using multimedia may improve adherence but not patient outcomes: a systematic review and meta-analysis

Abstract: Objective: To determine whether patients have better outcomes when exercise instructions are provided using multimedia approaches compared with verbal or written instructions. Data sources: Electronic databases (MEDLINE, EMBASE, CINAHL, and PsychInfo) searched up to October 2018. Study selection: Randomized controlled trials exploring exercise-based interventions for health conditions, and comparing instructions provided using multimedia approaches with conventional verbal or written instructions. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 39 publications
0
3
0
2
Order By: Relevance
“…Compared with previous studies, our participants received only one face-to-face instruction and then followed the instructional videos to practice cervical stabilization exercises thrice weekly. Previous studies have shown that multimedia-based exercise instructions can improve understanding and adherence to exercises [ 30 , 31 ]. Considering our positive results, instructional videos may be an effective and cost-efficient method for delivering cervical stabilization exercises.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with previous studies, our participants received only one face-to-face instruction and then followed the instructional videos to practice cervical stabilization exercises thrice weekly. Previous studies have shown that multimedia-based exercise instructions can improve understanding and adherence to exercises [ 30 , 31 ]. Considering our positive results, instructional videos may be an effective and cost-efficient method for delivering cervical stabilization exercises.…”
Section: Discussionmentioning
confidence: 99%
“…5 The international community of researchers 6 and clinicians continue to develop our understanding of exercise in pwMS and work towards identifying the most effective exercise interventions for people with a range of disability 7,8,1,9,10 and in a range of settings. [11][12][13] For example, over the past twenty years interventions to enhance long-term engagement with activity [14][15][16] have been developed and evaluated and the value of incorporating behavioural interventions to support behaviour change has been investigated. [17][18][19] These developments are vital since sustained engagement in exercise is required to retain any benefits gained.…”
Section: Introductionmentioning
confidence: 99%
“…Offering exercise programs facilitated by technology and videos has been previously investigated for people with stroke [14,15] and in wider populations [16][17][18]. Videoguided exercise has been demonstrated to impact adherence but not outcomes over more traditional paper or booklet programs [18]. Furthermore, it has been found feasible for people with health conditions to access videos on an iPad, though not all liked using them [17].…”
Section: Discussionmentioning
confidence: 99%